FREQUENCY OF MICROALBUMINURIA IN ABNORMAL LIPID METABOLISM AND SUFFERING FROM TYPE II DIABETES MELLITUS - Ali, Ejaz; Khattak, Abdul Latif; Khan, Andaleeb; Butt, Kamil Rehman; Yousafzai, Raheel Akhtar; Tariq, Abdul Moeed (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the frequency of dyslipidaemia in type-2 diabetic patients and to compare the frequency of dyslipidaemia in patients with and without microalbuminuria in type 2 diabetes.Study Design: cross-sectional study.Place and Duration of Study: Department of General Medicine, Combined Military Hospital Quetta Pakistan, from Dec 2018 to Jun 2019.Methodology: All patients who fulfilled the inclusion criteria and visited General Medicine department of Combined Military Hospital Quetta with type II diabetes mellitus were included in the study. Blood sample following an 8-12 hours fasting over the last night and 24 hour urine sample for microalbuminuria was collected to assess the outcome i.e. frequency of dyslipidaemia and also its frequency with and without microalbuminuria.Result: A total of 165 patients with type 2 diabetes mellitus were included. Ninety nine (60%) were males and 66 (40%) were females with the mean age of 48.08 ± 7.63 years. Overall, dyslipidaemia was found in 48 (29.1%) patients, dyslipidaemia was noted in 29 (17.6%) with microalbuminuria and 19 (11.5%) without microalbuminuria. Chi-square test revealed that dyslipidaemia was significantly more in patients of diabetes mellites having microalbuminuria than those not having it (p-value=0.01).Conclusion: Abnormal lipid metabolism was present in significantly more in patients with microalbuminuria as compared to those without microalbuminuria suffering from type II diabetes mellitus.